A Study on Worksite Marketing strategy and critical evaluation of its success potential for HDFC Standardlife Insurance Company Limited. - Albert Rozario, Arock Rufus (2010)
This report presents the facts and trends, the challenges on ‘Worksite Marketing’ and recommends suggestions to HDFC Standard Life Insurance Company Ltd for its successful implementation of the proposed strategy. The main objective of the study is to accomplish the following,  Proper understanding of life insurance industry in India  To deeply understand various distribution channels in practice and its effectiveness in the insurance market.  To insightfully understand the concepts of worksite marketing channel  To support HDFC – SLIC (Chennai), recommending for their successful implementation of the channel guided through proper understanding of the market via market study.